Pengaruh Pelaksanaan Sistem Manajemen Kesehatan dan Keselamatan Kerja (SMK3) Terhadap Kinerja Perawat di Ruang Operasi Rumah Sakit King Fahad Madinah Al-Munawwaroh - Kumala Fatma; Bernard Hasibuan; Ninin Gusdini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The work accident rate shows that it still occurs from 2019-2021 at 4-6% in the hospital environment, while the quality of service for health care facilities needs to be maintained and improved through one of them by implementing an occupational health and safety management system (SMK3) and optimizing the performance of nurses. which is the largest health worker in any health care facility. The purpose of the study was to determine the implementation of the health and safety management system, to determine the performance of nurses and to determine the effect of the implementation of the occupational health and safety management system on performance. The method in this study used a descriptive cross-sectional observational design with simple regression analysis and used a sampling technique using a total sampling of 35 nurses. The results of the research on the implementation of the occupational health and safety management system went in the good category by 80% while 20% went in the poor category and the overall nurse performance performed in the good category and there was a significant influence between the implementation of the occupational health and safety management system on the nurse's performance by 24, 5% while the rest is influenced by other factors. Hospitals need to design socialization programs, training workshops on SMK3 for every employee (nurse) at least once every six months to improve the implementation of SMK3 in the future can be in the very good category so that it can affect the performance of nurses more optimally in the very good category.